1994
DOI: 10.1002/ajmg.1320520407
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary hyperplasia in the Fraser cryptophthalmos syndrome

Abstract: We report on 2 sibs with the Fraser cryptophthalmos syndrome who had pulmonary hyperplasia and laryngeal stenosis. A third unrelated patient with Fraser syndrome had laryngeal stenosis, renal agenesis, and normal lung development, rather than the expected pulmonary hypoplasia. Three additional cases of pulmonary hyperplasia in the Fraser syndrome were ascertained from a review. In all of these cases the likely mechanism for pulmonary hyperplasia is retention of fetal lung fluid by laryngeal or tracheal obstruc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 53 publications
0
12
0
Order By: Relevance
“…Cardiac malformations included hypertrophy of the left ventricle, 33 hypertrophic heart, 16 a variant of Ebstein anomaly, 36 coarctation of the aorta, 4 an atrial septal defect, 37 an interventricular communication, 15 and a truncus arteriosus and a ventricular septal defect. 4 One patient had complex heart disease with dysplasia of the pulmonary and aortic valves and endocardial fibrosis.…”
Section: Cardiac Malformationsmentioning
confidence: 99%
“…Cardiac malformations included hypertrophy of the left ventricle, 33 hypertrophic heart, 16 a variant of Ebstein anomaly, 36 coarctation of the aorta, 4 an atrial septal defect, 37 an interventricular communication, 15 and a truncus arteriosus and a ventricular septal defect. 4 One patient had complex heart disease with dysplasia of the pulmonary and aortic valves and endocardial fibrosis.…”
Section: Cardiac Malformationsmentioning
confidence: 99%
“…Laryngeal stenosis or atresia is known to be associated with bilateral hyperechogenic and enlarged lungs in fetuses with isolated laryngeotracheal obstruction 30,31 . However, in fetuses with Fraser syndrome it does not necessarily lead to pulmonary hyperplasia as postulated by Stevens et al 9 , but can also be associated with pulmonary hypoplasia as shown in one case by Ramsing et al 4 , one case by Thomas et al 1 and four cases by Boyd et al 6 . Bilateral hyperechogenic lungs can also be caused by CCAML III 32 .…”
Section: Discussionmentioning
confidence: 91%
“…It is now recognised that not all infants with Fraser syndrome have cryptophalmos. Stevens et al (1994) observed pulmonary hyperplasia and laryngeal stenosis in two siblings with Fraser syndrome. Markedly enlarged echogenic lungs may be demonstrable on ultrasound in this condition.…”
Section: Fraser Syndrome (Fraser-cryptophthalmos Syndrome)mentioning
confidence: 92%